Laboratory verification of the properties of recycled fine aggregates and the effect of different replacement percentages on concrete properties - Leoš Joura; Zdeněk Prošek; Aleš Palička (Acta Polytechnica CTU Proceedings, 2024)
This research work deals with the issue of laboratory testing of commonly available recycled fine aggregates, namely concrete recyclate, mixed recyclate and brick recyclate. Their geometrical properties: granulometric composition and fine particle content, including physical properties: bulk density and water absorption are investigated. The tests themselves are carried out according to available standards, which are currently mainly standards for testing natural aggregates, and it is necessary to assess the suitability of these tests for recycled aggregates as well. The results found for concrete recyclates confirm the use of these standards to obtain the properties mentioned, but the bulk density and absorption tests are inconclusive in the case of mixed and brick recyclates. Subsequently, test concrete specimens were produced in which natural fine aggregate and concrete recyclate were substituted at 33, 66 and 100 %. A series of tests were performed on the hardened concrete: bulk density, absorption, porosity and compressive strength. From the results obtained, the use of concrete recyclate in concretes with the replacement of natural fine aggregate at 33% is suitable, without a significant reduction in the observed properties.